MRI Alzheimers Comparisons of Demented and Non-demented Adults using datamining - EL-FELLAH, SOKENA; IDRIS, HANA (Libyan International Medical University, Faculty of Information Technology, 2019)
Alzheimer’s is an inversable progressive brain disorder that slowly destroys memory and thinking skills. Alzheimer can be diagnosed using magnetic resonance imaging(MRI), a technique used to produce a detailed image of the anatomy(Brain). Using the process of data mining, which analyzes hidden patterns of data in different perspectives, a comparison will be made to show differences between MRI scans of younger adults and older adults. Before machine learning, extracting data needed human experts that often requires a lot of time, money and effort. So researchers are focusing on developing deep learning models for accurate disease diagnosis. Healthcare data mining tries to solve real world health problems in diagnosis and treatment diseases with the purpose of improving medical diagnosis, identifying the courses of the disease and predicting the patients’ health condition in the future.